An Efficient Nano Scale Sequential Circuits with Clock Inherent Capability in QCA For Fast Computation Paradigm - S. Lekashri; R. Ramya; A.N. Duraivel; K. Kalpana (International Journal of Computational and Experimental Science and Engineering, 2025)
Quantum-Dot Cellular Automata is a cutting-edge nanotechnology emerging in the globe, has supplanted the conventional CMOS technologies. Because it doesn’t use electric current, this method uses less power because of the Coulomb interaction. This sequential circuit design concept is the most challenging approach in the field of QCA technology. In this proposed study, to design a novel D type flip-flop with pulse generator is included. This plan involves the design of n-bit counter using frequency divider approach. In this approach a novel D flip-flop worked with pulse generator. The QCA Designer, which compares the simulation findings with the suggested constructed circuits, is used to implement the suggested technique. The QCA Designer E tool is used to verify the power usage, which forms the basis of the performance analysis. The suggested plan provides the lowest power and improved performance factors based on the examination of the current approaches.